The IDENTIFY study: the investigation and detection of urological neoplasia in patients referred with suspected urinary tract cancer – a multicentre observational study. (8th September 2021) - Khadhouri, Sinan; Gallagher, Kevin M.; MacKenzie, Kenneth R.; Shah, Taimur T.; Gao, Chuanyu; Moore, Sacha; Zimmermann, Eleanor F.; Edison, Eric; Jefferies, Matthew; Nambiar, Arjun; Mannas, Miles P.; Lee, Taeweon; et al.
Abstract : Objective: To evaluate the contemporary prevalence of urinary tract cancer (bladder cancer, upper tract urothelial cancer [UTUC] and renal cancer) in patients referred to secondary care with haematuria, adjusted for established patient risk markers and geographical variation. Patients and Methods: This was an international multicentre prospective observational study. We included patients aged ≥16 years, referred to secondary care with suspected urinary tract cancer. Patients with a known or previous urological malignancy were excluded. We estimated the prevalence of bladder cancer, UTUC, renal cancer and prostate cancer; stratified by age, type of haematuria, sex, and smoking. We used a multivariable mixed‐effects logistic regression to adjust cancer prevalence for age, type of haematuria, sex, smoking, hospitals, and countries. Results: Of the 11 059 patients assessed for eligibility, 10 896 were included from 110 hospitals across 26 countries. The overall adjusted cancer prevalence ( n = 2257) was 28.2% (95% confidence interval [CI] 22.3–34.1), bladder cancer ( n = 1951) 24.7% (95% CI 19.1–30.2), UTUC ( n = 128) 1.14% (95% CI 0.77–1.52), renal cancer ( n = 107) 1.05% (95% CI 0.80–1.29), and prostate cancer ( n = 124) 1.75% (95% CI 1.32–2.18). The odds ratios for patient risk markers in the model for all cancers were: age 1.04 (95% CI 1.03–1.05; P < 0.001), visible haematuria 3.47 (95% CI 2.90–4.15; P < 0.001), male sex 1.30 (95% CI 1.14–1.50; P < 0.001), and smoking 2.70 (95% CI 2.30–3.18; P < 0.001). Conclusions: A better understanding of cancer prevalence across an international population is required to inform clinical guidelines. We are the first to report urinary tract cancer prevalence across an international population in patients referred to secondary care, adjusted for patient risk markers and geographical variation. Bladder cancer was the most prevalent disease. Visible haematuria was the strongest predictor for urinary tract cancer.